SOME TECHNIQUES OF HISTORIOGRAPHIC METAFICTION IN THE NOVEL FLAUBERT’S PARROT BY JULIAN BARNES (Journal of Contemporary Philology, 2023)
This research is based on the interest to critically analyze and elaborate some of the techniques of historiographic metafiction that are present in the novel Flaubert’s parrot(1984) by Julian Barnes. The paper explores the hypothesis on how some techniques used in the aforementioned novel, such as fictionalizing Flaubert’s biography, the leap from the intended biography of Flaubert to an “unintended” autobiography of the narrator Braithwaite, the mixture of different citations and intertextuality, reflect how the past, history, literature and truth are perceived. The hypothesis uses the methods of analysis and synthesis. The conclusion should show us that the past and history are available in the form of written texts, that there is not just one, but many truths in the novel, that fact and fiction coexist and their borders are not erased, but rather blurred, and that a great deal of the book can be read as a parody of the biography genre.
Keywords: techniques; historiographic metafiction; Flaubert’s Parrot (novel); Julian Barnes; interpretation